Основні результати археологічних досліджень на Кінбурнській косі в 2009-2013 рр. - Біляєва, С.О.; Карашевич, І.В.; Фіалко, О.Є. (Археологія, 2014)
Подано результати археологічних досліджень комплексу пам’яток на Кінбурнській косі. На основі зіставлення археологічних, писемних і картографічних джерел визначено локалізацію фортеці османського часу та виділено основні етапи її розбудови та експлуатації. Представлены результаты археологических исследований комплекса памятников Кинбурнской косы в 2009— 2013 гг. Основное внимание уделено Кинбурнской крепости османского периода, местоположение кото рой определено авторами в ходе комплексных исследований. На основе сопоставления письменных, археологи ческих и картографических данных представлен исторический анализ основных строительных этапов крепости. Видимо, первая крепость на Кинбурне была возведена в Хvi в. Первые два этапа ее строительства и функциони рования определены как турецкие, третий связан с военной деятельностью россии.
Среди выявленных артефактов привлекает внимание серия монет, в том числе серебряная монета Филиппа iii (1598—1621) или Филиппа iv (1621—1665), монеты Крымского ханства, Османской и российской империи Xviii— XiX вв., детали одежды (пуговицы, пряжки), бытовые предметы (курительные трубки, глиняная, сте клянная и бронзовая посуда), предметы вооружения (пули разных типов, ядра, шомполы и др.). Примечательно, что бытовые предметы представляют культуру двух этносов — османского и украинского, а русское присутствие засвидетельствовано изделиями военного назначения, обмундирования и монетами.
В целом находки датируются Xvi—XiX вв. и являются характерными для крепостных комплексов Северного Причерноморья. Presented are the results of archaeological study of a set of monuments at kinburn spit in 2009—2013. the main atten tion was paid to the Ottoman period kinburn fortress, the localization of which was defined by the authors during the comprehensive research. Based on the comparison of the written, archaeological, and cartographic data the historical analysis of the main construction periods of the fortress was presented. apparently, the first fortress at kinburn was erected in the 16th c. the first two periods of its building and functioning are determined as turkish, and the third one is related with russia’s military activity.
among the artefacts discovered, of special interest are a series of coins including a silver coin of Philip iii (1598— 1621) and Philip iv (1621—1665), the Crimean khanate coins, of the 18th c. and the 19th c. Ottoman and russian em pires coins, the details of clothes (buttons and buckles), everyday used items (pipes and clay, glass, and bronze vessels), arms (bullets of various types, balls, ramrods, etc.). noteworthy is the fact that everyday used items represent the cultures of two ethnic groups: Ottoman and Ukrainian ones, while the russian presence is testified by the products of military purpose, uniform, and coins.
in general, the finds are dated by the period from the 16th c. to the 19th c. and are peculiar for the fortified assemblages of the Black sea north region.